PENGARUH PENGGUNAAN KAFEIN TERHADAP VO2Max DAN DENYUT NADI SETELAH LATIHAN PADA ATLET JUNIOR KARO TAEKWONDO CLUB - Julius Boy Nesra Basgimata Barus; Janwar Frihasan Sinuraya; Tommy Hejeprinta (Universitas Quality, 2022)
Coffee is a psychostimulant drink used by athletes as a supplement when they are training, because the coffee content affects physical activity with the content of the CNS in it. In addition, the methylxanthine group contained in caffeine has an effect on increasing heart rate and frequency. So that the positive benefits arising from the use of coffee became the basis for conducting this research. The purpose of this study was to determine the effect of caffeine use on VO2max and pulse rate after exercise in Junior Karo Taekwondo Club athletes. This research is an experiment with a research design